A comparative study of the clinical efficacy and safety of timolol 0.5% and travoprost 0.004% eye drops in primary open angle glaucoma - Bakkewar, Shweta M.; Tamboli, Saleem B.; Sahasthrabudhe, Vivek M. (International Journal of Research in Medical Sciences, 2018)
Background: Raised intraocular pressure (IOP) is a strong risk factor for development of glaucoma. If the condition is detected early enough it is possible to arrest the development or slow the progress with medication that lowers IOP. Travoprost is a newer prostaglandin analogue lowers IOP by facilitating outflow of aqueous humor. Methods: This was a prospective, randomized, open labelled, parallel group study, in which sixty cases of newly diagnosed primary open angle glaucoma (POAG) were included. After baseline clinical evaluation 30 subjects of glaucoma were treated with timolol 0.5% eye drop while another 30 subjects were given travoprost 0.004% eye drop and followed for 1 month to see IOP lowering efficacy of the two drugs. Statistical analysis was done using Open Epi 2.3 version for paired t test and unpaired t test. Results: In subjects treated with timolol eye drop mean reduction of IOP from baseline to week 4 was by 6.6mmHg while that of travoprost treated subjects was by 8.07mmHg. There was significant reduction in mean IOP of study subjects in travoprost group as compared to timolol group (P<0.05). Conclusions: Both timolol 0.5% and travoprost 0.004% eye drops are effective in reducing intra ocular pressure in POAG. On comparison travoprost was found to be statistically superior to timolol in lowering IOP in patients with POAG.